2014
DOI: 10.3945/jn.114.196105
|View full text |Cite
|
Sign up to set email alerts
|

Insufficient Intake of L-Histidine Reduces Brain Histamine and Causes Anxiety-Like Behaviors in Male Mice

Abstract: L-histidine is one of the essential amino acids for humans, and it plays a critical role as a component of proteins. L-histidine is also important as a precursor of histamine. Brain histamine is synthesized from L-histidine in the presence of histidine decarboxylase, which is expressed in histamine neurons. In the present study, we aimed to elucidate the importance of dietary L-histidine as a precursor of brain histamine and the histaminergic nervous system. C57BL/6J male mice at 8 wk of age were assigned to 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(35 citation statements)
references
References 39 publications
1
34
0
Order By: Relevance
“…Among them, APH‐8 and APH‐2 exhibited resembled escape latency and error times to the piracetam group. High content of Glu in APH‐8 might be a reason for its good effects on impaired mice brain, which was also found in cerebrolysin (Rockenstein et al ., ), while Asp, Ser and His were reported to be useful in improving cognitive deficits (Butcher et al ., ; Bado et al ., ; Yoshikawa et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…Among them, APH‐8 and APH‐2 exhibited resembled escape latency and error times to the piracetam group. High content of Glu in APH‐8 might be a reason for its good effects on impaired mice brain, which was also found in cerebrolysin (Rockenstein et al ., ), while Asp, Ser and His were reported to be useful in improving cognitive deficits (Butcher et al ., ; Bado et al ., ; Yoshikawa et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…Another possible role of carnosine in the brain has suggested that it acts as a reservoir for histidine, which is a precursor for histamine (Zhu et al 2007 ). Decreases in histidine has been demonstrated to reduce brain histamine levels and subsequently increase anxiety-like behaviors (Yoshikawa et al 2014 ), reduce cognitive function (Dai et al 2007 ) and contribute to stress and depression (Yanai et al 1998 ). When histamine levels are elevated levels of anxiety appear to be reduced (Endou et al 2001 ), and memory task capability appears to be maintained (Benetti and Izquierdo 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…According to several studies, dietary HIS affects histamine concentrations in immune cells, the stomach, and the brain [58][59][60][61]. Altered function of the immune system, allergic reactions, and/or peptic ulcers have not been reported after HIS administration.…”
Section: Effects Of Dietary His On Histamine Levelsmentioning
confidence: 99%
“…Several studies have reported an anorectic effect of HIS administration [65][66][67][68] and HIS-enriched diet [62][63][64]. Insufficient HIS intake reduces the brain histamine content and is associated with anxiety-like behaviors in mice [61].…”
Section: Effects Of Dietary His On Histamine Levelsmentioning
confidence: 99%